(untitled) (Fiep Bulletin - online, 2014)
This study deals with the nature of dance at school in a perspective of transformation. The new school curricula of early childhood, based on PCNs, which bring the trend to include creative forms of art (music, arts and dance) has had a prominent place in systematic and unsystematic education. Because of the educative methods and processes developed by these PCNs, children learn from the experiences with their own bodies to act freely in the space where they live, interacting with people around them. At school, dance is not considered a discipline but part of Physical Education or Arts Curricula. The present study investigated the introduction of Creative Dance at School, taking into consideration cultural and social aspects. Creative Dance is designed for boys and girls of age 03 to 06, mainly the shyest ones, as it aims at developing the knowledge of one own body, self-esteem and self-confidence. It was observed during this study that dance is a content that cannot be dissociated from the educative process as the pedagogical action may bring contributions to children’s development. It is necessary that children feel creative dance by the possibilities of creation and freedom of expression that it offers, in the sense of improving life quality, mainly in this period of child formation, when corporal and psychological methods are essential to the development of selfesteem, self-confidence and social skills.